Differential Expression of MicroRNA (MiR-27, MiR-145) among Dental Pulp Stem Cells (DPSCs) Following Neurogenic Differentiation Stimuli - Charlton Bassett; Hunter Triplett; Keegan Lott; Katherine M. Howard; Karl Kingsley (Biomedicines, 2023)
This study sought to evaluate the expression of previously identified microRNAs known to regulate neuronal differentiation in mesenchymal stem cells (MSCs), including miR-27, miR-125, miR-128, miR-135, miR-140, miR-145, miR-218 and miR-410, among dental pulp stem cells (DPSCs) under conditions demonstrated to induce neuronal differentiation. Using an approved protocol, n = 12 DPSCs were identified from an existing biorepository and treated with basic fibroblast growth factor (bFGF) and epidermal growth factor (EGF), which were previously demonstrated to induce neural differentiation markers including Sox1, Pax6 and NFM among these DPSCs. This study revealed that some microRNAs involved in the neuronal differentiation of MSCs were also differentially expressed among the DPSCs, including miR-27 and miR-145. In addition, this study also revealed that administration of bFGF and EGF was sufficient to modulate miR-27 and miR-145 expression in all of the stimulus-responsive DPSCs but not among all of the non-responsive DPSCs—suggesting that further investigation of the downstream targets of these microRNAs may be needed to fully evaluate and understand these observations.